2019
DOI: 10.1108/ijlss-09-2017-0103
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma in Brazil: a literature review

Abstract: Purpose This paper aims to investigate Lean Six Sigma (LSS) in the Brazilian context, seeking to identify its main characteristics and opportunities for future research. Design/methodology/approach This study focuses on a literature review in the area of production engineering and operations management, where 104 relevant scientific publications were identified. Findings The results show that the most important critical success factor for integrating LSS in Brazil is top management support and commitment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 85 publications
1
43
0
Order By: Relevance
“…At an operational level within the manufacturing sector, the LSS model aims to clarify the process of identifying opportunities, as well as reduce variability and improve the quality of the manufacturing process (Muganyi et al, 2019;Holmes, et al, 2015). By utilising the LSS five-phased systematic methodology of DMAIC (Define, Measure, Analysis, Improve, Control), integrated with five general phases of project management (initiation, planning, execution, control and closing), manufacturers can tackle their own specific problems (Walter and Paladini, 2019;Sreedharan and Sunder, 2018;Marques and Matthe, 2017;Tenera and Pinto, 2014;and Gupta, et al, 2012). One of the most crucial steps of the LSS project is to identify the customer demand or voice of the customer and translate it to a prioritised Critical to Quality (CTQ) metric (Tenera andPinto, 2014 andLighter, 2014) that serves as the outcome variable.…”
Section: Lean Six Sigma In the Manufacturing Sectormentioning
confidence: 99%
“…At an operational level within the manufacturing sector, the LSS model aims to clarify the process of identifying opportunities, as well as reduce variability and improve the quality of the manufacturing process (Muganyi et al, 2019;Holmes, et al, 2015). By utilising the LSS five-phased systematic methodology of DMAIC (Define, Measure, Analysis, Improve, Control), integrated with five general phases of project management (initiation, planning, execution, control and closing), manufacturers can tackle their own specific problems (Walter and Paladini, 2019;Sreedharan and Sunder, 2018;Marques and Matthe, 2017;Tenera and Pinto, 2014;and Gupta, et al, 2012). One of the most crucial steps of the LSS project is to identify the customer demand or voice of the customer and translate it to a prioritised Critical to Quality (CTQ) metric (Tenera andPinto, 2014 andLighter, 2014) that serves as the outcome variable.…”
Section: Lean Six Sigma In the Manufacturing Sectormentioning
confidence: 99%
“…Lean and Six Sigma are the two most important continuous improvement (CI) methodologies for achieving operational and service excellence in any organization [29][30][31][32][33]. LSS is the fusion of two most powerful process excellence methodologies, namely, Lean and Six Sigma [24].…”
Section: Integrating Lean and Six Sigmamentioning
confidence: 99%
“…Lean six sigma consists of many tools and techniques for continuous improvement such as the Kanban system, 5S, Cause and Effect analysis (C&E), Value Stream Mapping (VSM) and many others [35,36]. According to Brazilian publications, there are six most frequently tools used in LSS applications: "Control Charts", followed by "Value Stream Mapping", "DMAIC," "Kaizen," "Ishikawa Diagram," and "Histogram;" and Control chart is the top ranking tool [33]. DMAIC is a five step Lean Six Sigma in Manufacturing: A Comprehensive Review DOI: http://dx.doi.org/10.5772/intechopen.89859 method for improving existing process problems with unknown causes.…”
Section: Tools and Techniquesmentioning
confidence: 99%
“…Also, Mahanti and Antony (2009) found that statistical process control, control charts, fishbone diagram, gap analysis, capability maturity model, regression, process mapping, QFD, failure mode and effect analysis (FMEA) and process capability analysis are among the most used tools in the software industry setting. In their literature review on Brazilian studies, Walter and Paladini (2019) state that the most frequently used tools in lean Six Sigma applications are control charts, value stream mapping, Ishikawa diagram and histogram. On the other hand, their study show that Six Sigma techniques such as ANOVA, regression analysis, hypothesis testing, gage R&R analysis and confidence intervals were not frequent (Walter and Paladini, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In their literature review on Brazilian studies, Walter and Paladini (2019) state that the most frequently used tools in lean Six Sigma applications are control charts, value stream mapping, Ishikawa diagram and histogram. On the other hand, their study show that Six Sigma techniques such as ANOVA, regression analysis, hypothesis testing, gage R&R analysis and confidence intervals were not frequent (Walter and Paladini, 2019).…”
Section: Introductionmentioning
confidence: 99%